PENGEMBANGAN BUKU SISWA BERCIRIKAN OPEN ENDED MATHEMATICS PROBLEM UNTUK MEMBANGUN BERPIKIR KREATIF - Octavina Rizky Utami Putri (Universitas Muhammadiyah Ponorogo, 2017)
The aim of this research and development is to produce a students book characterized with open ended mathematics problem to build creative thinking. The specification of this students book lies in the given problem is loading open problems that can be completed providing with many answers. This research and development uses 4D model by Thiagarajan, et al. (1974), that is define, design, and develop. Instruments and RPP were also developed to support students book development. This students book has met the valid, practical, and effective criteria and can build students' creative thinking. This is demonstrated by more than 70% of students have met the minimal creative category, so that students' creative thinking has been awakened. Keywords: student book, open ended problem, creative thinking